Analisis Efektivitas dan Efisiensi Pengelolaan Keuangan Terhadap Transparansi Penggunaan Dana DIPA pada Unit Kegiatan Mahasiswa Kronika IAIN Metro - Arta Marsha Putri; Irsyad Azis Ardiansyah; Mellisa Wulandari; Salva Febrian Eka Putra (Jurnal Ekonomi, Akuntansi, dan Perpajakan, 2024)
This research aims to analyze the effectiveness and efficiency of the DIPA fund financial management system on the transparency of the use of UKM kronika. This type of research uses a qualitative approach with descriptive methods. The data sources used in this research are primary data through field observations and in-depth interviews, as well as secondary data from related documents. The results of the research show that the effectiveness of the DIPA Fund financial management system in chronic UKM is still not optimal, as can be seen from inadequate planning, minimal community involvement, and indications of misuse of funds. In terms of efficiency, it was found that there was convoluted bureaucracy, lack of supervision and cost control, and not optimal use of information technology.